Bacterial Pathogens Associated with Periodontitis in Diabetic and Non-Diabetic Patients - Hazim, Farukh Abu; Yasmin, Rizwana; Harani, Mahadev (Infectious Diseases Journal of Pakistan, 2023)
Background: The aim of study was to evaluate that whether diabetic patient having periodontitis are more susceptible to certain classes of bacteria especially anaerobes as compared to non-diabetic. The study is clinically significant because of its implication in the treatment of bacterial periodontitis in diabetic and non-diabetic patients. Methods: The study was conducted in the department of microbiology, Basic Medical Science Institute, (BMSI), Jinnah Postgraduate Medical Center Karachi (JPMC) & Abbasi Shaheed Hospital. 30 samples were collected from JPMC and 70 samples from Abbasi Shaheed Hospital from 2012 to 2014 This study was carried out on pus sample taken from periodontal pocket of diabetic (n- 50) and non-diabetic (n- 50) patients. Samples were collected from each patient using a sterile cotton swab at the site of lesion in the oral cavity and processed in aerobic and anaerobic condition. Bacteria were isolated and identified by standard laboratory methods. Result: Most (97%) samples yielded a positive culture; no bacteria were isolated in 3 samples, 57 samples were positive for anaerobic bacteria; 40 samples had mixed growth of aerobes and facultative anaerobic bacteria. Conclusion: The findings of the present study indicate that anaerobic pathogens are more common in diabetic patients with periodontitis. Among them Prevotelladenticolla and Petostreptococcusanerobicus were more frequent isolates. Keywords: Periodontitis, bacterial flora, diabetes mellitus,